3D printed biodegradable implants as an individualized drug delivery system for local chemotherapy of osteosarcoma. (15th January 2020) - Wang, Yonghui; Sun, Liang; Mei, Zhigang; Zhang, Fazhou; He, Meifang; Fletcher, Cameron; Wang, Fenglong; Yang, Jingjing; Bi, Dongbin; Jiang, Yanyan; Liu, Ping
Abstract: A 3D printing technique has been developed which enables the treatment of osteosarcoma via personalized local chemotherapy. A series of in vivo trials were conducted which closely mimicked real clinical chemotherapeutic conditions. We have shown that 3D printed poly L-lactic acid (PLLA) implants are exceptional carriers for anticancer drugs and can be designed with finely tuned physical morphologies and controllable micropore structures. Their favorable biodegradability, in vitro cytotoxicity, in vitro blood compatibility, in vivo subacute toxicity, and in vivo sensitization tests have confirmed their biocompatibility and pharmaceutical properties. Furthermore, we have demonstrated that local chemotherapy with the assistance of the as-prepared PLLA implant exhibits an anti-osteosarcoma efficacy superior to traditional chemotherapy through a series of in vivo anti-osteosarcoma tests according to clinical protocols. The proposed 3D printed drug delivery system can simultaneously realize individual local chemotherapy, multi-drug delivery, long-term sustainable drug release, and non-reoperation in osteosarcoma treatment. Our studies enable the utilization of the 3D printing technique in the treatment of osteosarcomas and guide future clinical trials. The established techniques and principles can also be adapted to the local chemotherapy of other tumors. Graphical abstract: Unlabelled Image Highlights: 3D printed PLLA drug carriers could realize the possibility of personalized local chemotherapy in the treatment of osteosarcoma. 3D rapid prototypes suggested that the spherical implant should be more favorable for the anticancer drug delivery. As a local chemotherapy, this novel 3D printed drug administration system has many other advantages.